2011
DOI: 10.1016/j.canlet.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of mucins in the skin during benign and malignant conditions

Abstract: Skin related diseases comprise a major health challenge to the practicing physician, and constitute a significant psychological, social and financial burden to the society. Further, skin cancer, especially non-melanoma skin cancer is currently the leading type of malignancy in the Western world. Given the huge burden of skin diseases, there is growing emphasis on understanding their pathophysiology, and towards their early detection. Mucins are high molecular weight O- and N-linked glycoproteins that have emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 117 publications
1
33
1
9
Order By: Relevance
“…They have recently been shown to play a role in both benign and malignant skin conditions. 28 MUC15 was found to be overexpressed in patients with metastatic melanoma, 28,29 and structural motifs in MUC15 have been identified as being epidermal growth factor receptor. 29 Interestingly, a recent study of gene expression in canine AD has shown a significant increase in MUC15 expression in lesional skin from dogs with AD when compared with that seen in healthy control animals.…”
Section: Discussionmentioning
confidence: 98%
“…They have recently been shown to play a role in both benign and malignant skin conditions. 28 MUC15 was found to be overexpressed in patients with metastatic melanoma, 28,29 and structural motifs in MUC15 have been identified as being epidermal growth factor receptor. 29 Interestingly, a recent study of gene expression in canine AD has shown a significant increase in MUC15 expression in lesional skin from dogs with AD when compared with that seen in healthy control animals.…”
Section: Discussionmentioning
confidence: 98%
“…Some genes originally included as mucins have now been renamed following the recognition that they do not fulfill the classic criteria for a mucin. One such protein is MUC18 (now known as m elanoma c ell a dhesion m olecule or MCAM) that belongs to the immunoglobulin superfamily of proteins [19]. …”
Section: Mucinsmentioning
confidence: 99%
“…Epithelial mucins could be structurally divided into two families: membrane-tethered mucins (e.g., MUC1, MUC3A, MUC3B, and MUC4) and secreted or gel-forming mucins (e.g., MUC2, MUC5AC, and MUC5B). 6,7 Under physiological conditions, tissue-specific expressions of MUC, particularly in the aerodigestive and genitourinary system, have been found to play an essential role in lubricating and protecting the epithelial and body lumens against harmful exogenous and endogenous environmental stresses (e.g., bacteria, drugs, and toxins) and also in cellular adhesion, differentiation, and immunity via transmitting growth and survival signals to the interior of the cell. 8 Mounting evidence, however, indicates that the levels of MUCs are significantly deregulated during carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%